Treatment of corneal disease with traditional Tibetan medicine: A report of four cases - Yangkyi, Tseten; Waller, Stephen G (Nepalese Journal of Ophthalmology, 2011)
DOI: 10.3126/nepjoph.v3i1.4284Nepal J Ophthalmol 2011;3(5):83-85